Spatiotemporal delivery of nanoformulated liraglutide for cardiac regeneration after myocardial infarction - Qi Q (Dove Medical Press, 2017)
Quan Qi,1,* Lei Lu,2,3,* Haiqing Li,1,* Zhize Yuan,1 Gaoxian Chen,2,3 Miao Lin,2,3 Zhengwen Ruan,4 Xiaofeng Ye,1 Zeyu Xiao,2,3,5 Qiang Zhao1 1Department of Cardiac Surgery, Rui Jin Hospital, 2Department of Pharmacology, Institute of Medical Sciences, 3Translational Medicine Collaborative Innovation Center, Shanghai Jiao Tong University School of Medicine, Shanghai, 4Department of Cardiology, Yuyao People’s Hospital, Yuyao, Zhejiang, 5Collaborative Innovation Center of Systems Biomedicine, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: The local, intramyocardial injection of proteins into the infarcted heart is an attractive option to initiate cardiac regeneration after myocardial infarction (MI). Liraglutide, which was developed as a treatment for type 2 diabetes, has been implicated as one of the most promising protein candidates in cardiac regeneration. A significant challenge to the therapeutic use of this protein is its short half-life in vivo. In this study, we evaluated the therapeutic effects and long-term retention of liraglutide loaded in poly(lactic-co-glycolic acid)–poly(ethylene glycol) (PLGA–PEG) nanoparticles (NP-liraglutide) on experimental MI. PLGA–PEG nanoparticles (NPs) have been shown to efficiently load liraglutide and release bioactive liraglutide in a sustained manner. For in vitro test, the released liraglutide retained bioactivity, as measured by its ability to activate liraglutide signaling pathways. Next, we compared the effects of an intramyocardial injection of saline, empty NPs, free liraglutide and NP-liraglutide in a rat model of MI. NPs were detected in the myocardium for up to 4 weeks. More importantly, an intramyocardial injection of NP-liraglutide was sufficient to improve cardiac function (P<0.05), attenuate the infarct size (P<0.05), preserve wall thickness (P<0.05), promote angiogenesis (P<0.05) and prevent cardiomyocyte apoptosis (P<0.05) at 4 weeks after injection without affecting glucose levels. The local, controlled, intramyocardial delivery of NP-liraglutide represents an effective and promising strategy for the treatment of MI. Keywords: spatiotemporal delivery, nanoformulated liraglutide, cardiac regeneration